Scaling Agile with Jira Align​ : A practical guide to strategically scaling agile across teams, programs, and portfolios in enterprises /: A practical guide to strategically scaling agile across teams, programs, and portfolios in enterprises. (2020) - MacNeil, Dean; Cader, Aslam
No abstract available